2017
DOI: 10.1097/gox.0000000000001256
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Palate Repair without Lateral Relaxing Incision

Abstract: Background:The goals of successful palate repair include optimization of speech and feeding, avoidance of fistula formation, and mitigation of adverse maxillary growth. However, the effects of scar formation on maxillary growth have not been discussed in detail.Methods:Between November 2010 and December 2011, the palateplasty was performed for 24 patients with cleft palate (median age, 12 months; range, 11–18 months). In the velum, a symmetrical intravelar veloplasty with mucosal Z-plasty was performed on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…As we assessed the experience of a single senior surgeon working in a hospital considered as a high-volume center, [48] any extrapolation of the findings should be carried out with caution. Similar to previous studies, [30,[35][36][37][38][39][40][41][42][43][44][45] the intraoperative judgment and decisionmaking regarding the grade of tension in the midline and the need for lateral relaxing incision was subjective and dependent on the experience of each surgeon. Since, all patients were included in the last 3 years of practice, the clinical judgment of the senior surgeon can be considered constant in both the evaluated periods.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…As we assessed the experience of a single senior surgeon working in a hospital considered as a high-volume center, [48] any extrapolation of the findings should be carried out with caution. Similar to previous studies, [30,[35][36][37][38][39][40][41][42][43][44][45] the intraoperative judgment and decisionmaking regarding the grade of tension in the midline and the need for lateral relaxing incision was subjective and dependent on the experience of each surgeon. Since, all patients were included in the last 3 years of practice, the clinical judgment of the senior surgeon can be considered constant in both the evaluated periods.…”
Section: Discussionmentioning
confidence: 71%
“…[30,[35][36][37][38][39][40][41][42][43][44][45] Most of the previous studies as well as the present investigation have reported only early outcomes such as surgeryrelated complications including the fistula rate, while others have also demonstrated satisfactory speech outcomes. [30,[35][36][37][38][39][40][41][42][43][44][45] Although some mixed results concerning long-term maxillary arch and/or midface status have been reported after minimal incision palatoplasty, this should still be the target of future investigations using only medial incision approaches. [30,[35][36][37][38][39][40][41][42][43][44][45] In these previous studies minimal incision or only medial incision repairs were addressed [30,[35][36][37][38][39][40][41][42][43]…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations